Simultaneous B1 and T1 mapping using spiral multislice variable flip angle acquisitions for whole‐brain coverage in less than one minute. Issue 3 (12th November 2018) - Heule, Rahel; Pfeuffer, Josef; Meyer, Craig H.; Bieri, Oliver
Abstract : Purpose: Variable flip angle (VFA)‐based T1 quantification techniques are highly sensitive to B1 inhomogeneities and to residual T2 dependency arising from incomplete spoiling. Here, a rapid spiral VFA acquisition scheme with high spoiling efficiency is proposed for simultaneous whole‐brain B1 and T1 mapping. Methods: VFA acquisitions at 2 different flip angles are performed to quantify T1 using a steady‐state prepared spiral 2D multislice spoiled gradient‐echo sequence with the acquisition of 10 and 20 spiral interleaves at 1.5T and 3T, respectively. Additionally, parallel imaging acceleration of factor 2 is investigated at 3T. The free induction decay induced by the preparation pulse is sampled by a single‐shot spiral readout to quantify B1 . Results: The in vitro and in vivo validations yielded good agreement between the derived spiral VFA B1 and the acquired reference B1 maps as well as between the B1 ‐corrected spiral VFA T1 and the reference T1 maps. The spiral VFA acquisitions in the human brain delivered artifact‐free B1 and T1 maps and demonstrated high reproducibility at 1.5T and 3T. Conclusion: Reliable simultaneous spiral VFA B1 and T1 quantification was feasible with acquisition times of <1 min for whole‐brain coverage at clinically relevant resolution.